1943
DOI: 10.1084/jem.77.3.277
|View full text |Cite
|
Sign up to set email alerts
|

Ten Amino Acids Essential for Plasma Protein Production Effective Orally or Intravenously

Abstract: When blood plasma proteins are depleted by bleeding with return of the washed red cells (plasmapheresis) it is possible to bring dogs to a steady state of hypoproteinemia and a constant level of plasma protein production if the diet protein intake is controlled and limited. Such dogs are outwardly normal but have a lowered resistance to infection and to certain intoxications. When the protein intake of such dogs is completely replaced by the growth mixture (Rose) of crystalline amino acids, plas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
14
0

Year Published

1944
1944
2016
2016

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(20 citation statements)
references
References 14 publications
(17 reference statements)
5
14
0
Order By: Relevance
“…These experiments follow the same general pattern of those in previous reports (11,12). A dog is standardized for tests of plasma protein production by a process of body protein and plasma protein depletion.…”
Section: Methodssupporting
confidence: 55%
See 2 more Smart Citations
“…These experiments follow the same general pattern of those in previous reports (11,12). A dog is standardized for tests of plasma protein production by a process of body protein and plasma protein depletion.…”
Section: Methodssupporting
confidence: 55%
“…Certainly the low urinary nitrogen levels of such periods as 8, 9, 10, 16, and 17 suggest very good utilization of the injected amino acids. Data previously presented and discussed (11) suggest that 4.5 gm. is the approximate urinary nitrogen output of the minimal nitrogen metabolism of this dog.…”
Section: Amino Acid Injection Experiments--(tablesmentioning
confidence: 74%
See 1 more Smart Citation
“…He showed that sugar-fed animals could produce plasma proteins at the cost of tissue and, conversely, could maintain muscle mass, good health, and sustained nitrogen equilibrium when transfused only with plasma proteins (1). Within a decade it was shown that the sole protein derivatives that are both essential and sufficient to maintain health and nitrogen equilibrium were the amino acids (AAs) 8 threonine, valine, leucine, isoleucine, lysine, tryptophan, phenylalanine, methionine, and histidine-the "essential" AAs (EAAs) (2). By the 1970s, in vitro work in skeletal muscle preparations provided evidence that the role of AAs may not simply be as substrates for protein synthesis, with each having the potential to limit synthesis dependent on availability and the relative contribution of tissues (3).…”
Section: Introduction-a Brief History Of the Role Of Amino Acids In Smentioning
confidence: 99%
“…Evidence from experiments in dogs indicates that tryptophane plays a role in the formation of plasma proteins (6) and hemoglobin (3,4,7). In tryptophane deficiency produced experimentally for periods of 2 to 5 weeks in human subjects, one of us (M. M. W.) working with the first mentioned workers (1) was unable to demonstrate significant alterations in the red cells.…”
mentioning
confidence: 99%